Temporal dynamics of hemispheric interactions in visual word recognition using a repetition priming paradigm: modulation by stimulus onset asynchrony - Kim, Sangyub; Nam, Kichun (Frontiers in Psychology, 2025)
IntroductionUnderstanding how the two cerebral hemispheres interact during visual word recognition is central to describing the temporal and spatial dynamics of language processing. This study examined the role of stimulus onset asynchrony (SOA) in modulating interhemispheric interactions during a primed-lateralized lexical decision task. We focused on how the timing between prime and target presentations influences the contributions of the left and right hemispheres, using word familiarity.MethodParticipants performed a lexical decision task involving lateralized prime-target word pairs. Stimuli were presented either to the left visual field (LVF) or the right visual field (RVF) across three SOA conditions: 0 ms (simultaneous), 100 ms, and 200 ms (sequential). Word familiarity served as an indicator of lexical proficiency to assess hemispheric involvement across different temporal intervals. Interhemispheric interaction was inferred from performance patterns across visual field pairings and SOAs.ResultsAt a 100 ms SOA, when primes were presented to the LVF and targets to the RVF, response patterns indicated dominant involvement of the right hemisphere's visual-perceptual system in initiating interhemispheric processing. In contrast, at a 200 ms SOA, when primes were shown to the RVF and targets to the LVF, results reflected a stronger influence of the left hemisphere's lexical-semantic processing mechanisms in modulating interhemispheric effects.DiscussionThese findings underscore the critical role of temporal dynamics in shaping hemispheric contributions to visual word recognition. The differential effects observed at 100 ms and 200 ms SOAs suggest that interhemispheric integration is not static but time-sensitive, with each hemisphere showing varying degrees of influence depending on the temporal sequencing of activation. The results imply that lexical processing is contingent not only on visual field presentation but also on the precise timing of hemispheric engagement.